MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL MIND MAPPING KELAS V SD NEGERI 066050 MEDAN TAHUN PEMBELAJARAN 2024/2025 - Rio Samuel Nababan; Feri Haryati; Zuraida Hanum Lubis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to improve student learning outcomes through the application of the Mind Mapping learning model for class V of SD Negeri 066050 Medan for the 2024/2025 Academic Year. The subjects in the research were 20 fifth grade students. The techniques used by researchers in collecting data are observation and tests. The learning model used in this research is the Mind Mapping learning model. This research shows an increase in student learning outcomes in the science and science subjects SEEING FOR LIGHT, HEARING BECAUSE OF SOUND in Class V of SD Negeri 066050 Medan Baru for the 2024/2025 Academic Year. This is evident from the results of research conducted on the pretest (initial test) where 5 students got a complete score or 25%, while 15 students got an incomplete score or 75%, with an average learning result of 56.7. The research results in the first cycle increased to 8 students who completed or 40%, while 12 students or 60% did not complete, with an average score of 65. In the second cycle, student learning outcomes increased to 17 students or 85% of students who completed and those who did not complete. 3 students or 15% with an average score of 87, then there is an increase in cycle I to cycle II and has fulfilled the specified completion. Furthermore, from the results of observations of teacher activities in carrying out learning in cycle l, an average score of 72% (Good) was obtained and in cycle 2 it increased to 92% (Very Good) and the results of observations of student activities in cycle l obtained an average score of 62% (Good) and increased in the second cycle to 92% (Very Good). Thus, it was concluded that by using the Mind Mapping learning model there was an increase in student learning outcomes in the science and science subject in class V of SD Negeri 066050 Medan for the 2024/2025 academic year.